Pattern recognition receptors and their interactions with bacterial type III effectors in plants - Lee, Jae Hoon; Kim, Hyoungseok; Chae, Won Byoung; Oh, Man-Ho (SPRINGER, 2019)
Innate immune signaling of plants is initiated by pattern recognition receptors (PRRs) at the plasma membrane. Upon pathogen attack, PRRs recognize pathogen-associated molecular patterns (PAMPs) via ectodomain and lead to signaling cascade via cytoplasmic kinase domain. PAMP-triggered immunity (PTI) activates basal defense responses sufficient to confer broad-spectrum disease resistance by inhibiting pathogen entry and growth. On the other hand, one of the major virulence factors in plant-pathogenic bacteria is type III secretion system, which can deliver effector proteins into the host cell and modulate host cellular processes. Most type III effectors are implicated in PTI suppression, and PRRs have been identified as targets of multiple type III effectors. Mutants defective in T3SS lack pathogenicity in many bacterial species, revealing that T3SS-mediated PTI suppression is critical for host colonization and subsequent disease development. This review summarizes molecular basis of bacterial pathogen perception by plant PRRs and also interaction between PRRs and type III effectors during early stages of plant-pathogen interaction.